Islamic Sexuality Education for Early Childhood: Evaluating Flipped Learning Model with Parental Involvement in Indonesia - Nufus, Hayatun; Pratiwi, Hardiyanti; Yarliani, Ikta (Muadalah, 2025)
This study developed and evaluated an Islamic-based flipped learning model for early childhood sexuality education in South Kalimantan, Indonesia. The model integrates animated videos grounded in Islamic principles, addressing topics of body autonomy, privacy, and personal safety. Sixteen teachers and 96 children (aged 5–6) from four kindergartens participated. Using the ADDIE framework, the learning materials were designed and validated by experts (content validity = 4.8; media validity = 4.5). A quasi-experimental design compared the flipped learning model (47 children) with conventional storytelling using picture books (49 children). Both groups showed significant improvements between pretest and posttest (Wilcoxon Signed-Rank, p < 0.001). However, the experimental group outperformed the control group with higher posttest scores (M = 96.70 vs. 72.76; Mann-Whitney U = 102.000, Z = -7.933, p < 0.001, r = 0.81). These findings demonstrate that integrating Islamic values into a flipped learning approach, supported by parental involvement, is more effective than traditional methods. The model provides a culturally appropriate strategy for strengthening child protection and improving early sexuality education in Muslim-majority contexts.